2014
DOI: 10.1002/pc.22863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of exfoliated graphite nanoplatelets reinforced polyethylene terephthalate/polypropylene composites

Abstract: Exfoliated graphite nanoplatelets (GNP) reinforced composites materials based on blend of poly(ethylene terephthalate) (PET) and polypropylene (PP) were prepared by melt extrusion followed by injection molding. 10 parts per hundred resin (phr) styrene‐ethylene‐butylene‐styrene‐g‐maleic anhydride was added to the base formulation PET/PP (70/30) as a compatibilizer. PET/PP/GNP composites 0–5 phr were prepared and characterized using field emission scanning electron microscopy, transmission electron microscopy, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…A similar conclusion was arrived at by Inuwa et al [27]. Inuwa et al reported that there was no significant change in peak positions of PET/PP/GnP composites compared to pristine PET/PP blend.…”
Section: Fourier Transform Infrared (Ftir)supporting
confidence: 66%
See 1 more Smart Citation
“…A similar conclusion was arrived at by Inuwa et al [27]. Inuwa et al reported that there was no significant change in peak positions of PET/PP/GnP composites compared to pristine PET/PP blend.…”
Section: Fourier Transform Infrared (Ftir)supporting
confidence: 66%
“…In another study on epoxy/xGnP composite at low filler content of 0.1 wt%, a noticeable increment of 31% in modulus and 40% in fracture toughness was observed [26]. Recently, Inuwa et al [27] prepared xGnP reinforced Poly(ethylene terephthalate) (PET)/PP composites by melt blending method. The maximum flexural strength and impact strength of the composites were obtained at 3 phr xGnP loading.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of a small amount of GNP improved electrical [24,25], thermal [26,27], and mechanical properties significantly [28][29][30]. Thermal stability and flammability of polymer composites were also improved [31][32][33].…”
mentioning
confidence: 93%
“…Compared with nanoclays, GNPs have a similar layered structure but better mechanical properties. Compared to carbon nanotubes (CNTs), GNPs present similar excellent values of modulus, electrical and thermal conductivities, but higher surface area, lower cost and improved processability during composite fabrication [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous Poly(ethylene terephthalate) (aPET) is a thermoplastic polymer with good spinnability together with good mechanical properties, chemical resistance, thermal stability and low melt viscosity [4]. Amorphous PET is widely used in food packaging, film technology, automotive, electrical, beverages containers and textile fibers.…”
Section: Introductionmentioning
confidence: 99%